Effects of dietary oil blend on fatty acid composition, oxidative stability and physicochemical properties of Longissimus thoracis et lumborum muscle in goats - Adeyemi, Kazeem Dauda; Sabow, Azad Behnan; Abubakar, Ahmed Abubakar; Samsudin, Anjas Asmara @ Ab Hadi; Sazili, Awis Qurni (Japanese Society of Animal Science, 2016)
This study examined the effects of dietary blend of 80% canola oil and 20% palm oil (BCPO) on the physicochemical properties, antioxidant status, oxidative stability and fatty acid composition of Longissimus thoracis et lumborum (LTL) muscle from goats during chill storage. Over a 14-week feeding trial, 24 Boer bucks were randomly assigned to and supplemented with diets containing 0, 4 or 8% BCPO on a dry matter basis, slaughtered and the LTL was subjected to a 7 day chill storage. Neither diet nor post mortem ageing influenced (P > 0.05) antioxidant enzyme activities, chemical composition and cholesterol. Diet had no effect on the carbonyl content, free thiol content, water-holding capacity, tenderness, pH and glycogen. Oil-supplemented goats had higher (P < 0.05) C18:1 trans-11, C18:3n-3 and C20:5n-3, carotenoid, tocopherol and redness, and lower thiobarbituric acid reactive substances values than the control goats. Post mortem ageing decreased (P < 0.05) shear force and oxidative stability of chevon. No significant (P > 0.05) changes were found in the proportion of individual fatty acids throughout storage. Total polyunsaturated fatty acids (PUFA) decreased while total saturated fatty acids increased as storage progressed. Dietary BCPO enhanced n-3 PUFA without compromising the quality attributes of chevon.